THE MECHANISM OF ANAPHYLATOXIN FORMATION : STUDIES ON FERMENT ACTION. XV. - Jobling, James W. (The Rockefeller University Press, 1914)
1. The unsaturated lipoids (serum antitrypsin) can be adsorbed from guinea pig serum, rabbit serum, and horse serum by kaolin, starch, agar, and bacteria. 2. Diphtheria toxin and cobra venom also reduce the serum antitrypsin, possibly because of their affinity for lipoids. 3. Anaphylatoxins represent sera rendered toxic by partial removal of serum antitrypsin. 4. The matrix of the protein split products lies in the serum proteins so exposed. 5. The amount of removal of serum antitrypsin depends on definite quantitative relations; very large amounts and very small amounts of adsorbing substances are least effective (kaolin, starch, and bacteria). 6. Bacteria previously treated with serum or with oils do not adsorb serum antitrypsin. 7. Bacteria treated with serum become more resistant to the action of trypsin.